Erosion as a possible mechanism for the decrease of size of plastic pieces floating in oceans. (February 2018) - Resmeriță, Ana-Maria; Coroaba, Adina; Darie, Raluca; Doroftei, Florica; Spiridon, Iuliana; Simionescu, Bogdan C.; Navard, Patrick
Abstract: A sea water wave tank fitted in an artificial UV light weathering chamber was built to study the behaviour of polypropylene (PP) injected pieces in close ocean-like conditions. In air, the same pieces sees a degradation in the bulk with a decrease of mechanical properties, a little change of crystal properties and nearly no change of surface chemistry. Weathering in the sea water wave tank shows only a surface changes, with no effect on crystals or mechanical properties with loss of small pieces of matter in the sub-micron range and a change of surface chemistry. This suggests an erosion dispersion mechanism. Such mechanism could explain why no particle smaller than about one millimeter is found when collecting plastic debris at sea: there are much smaller, eroded from plastic surfaces by a mechano-chemical process similar to the erosion mechanism found in the dispersion of agglomerate under flow. Highlights: Polypropylene was weathered in ocean-like conditions with a UV sea water wave tank. Only surface changes are observed, contrary to weathering in air. Dispersion occurred by erosion, by a continuous detachment of sub-micron parts.